PENGARUH PELATIHAN TERHADAP KOMPETENSI KARYAWAN PT. LEN INDUSTRI (PERSERO) BANDUNG - Putu Ifo Yuda Wisastra; Ella Jauvani Sagala (Faculty of Economics and Business Udayana University, 2016)
This study aimed to analyze the influence of training on employee’s competency. This study was conducted at PT. Len Industri (Persero) Bandung. The sampling was using Slovin’s techniques with error rate 5%.The dataanalysis was using Path Analysis for this research and processed by using SPSS software ver.20 for windows. Data obtained by questionnaires to 192 employee respondents of PT. Len Industri (Persero) Bandung. The result showed that training variables had a significant influence on employee’s competency with simultaneously. But in partially, there’s didn’t have a significant influence on the employee’s competency. The variables that didn’t have a significant influence were training materials and trainees.